Differential Effect of Metal Ions on Antibacterial Activity of Chitosan Against Burkholderia cenocepacia - Li, B.; Fang, Y.; Shan, C.L.; Ibrahim, M.; Xie, G.L.; Wang, Y.L.; Sun, G.C. (Asian Journal of Chemistry, 2012)
In this study, the antibacterial activity of chitosan and chitosan metal salts against Burkholderia cenocepacia isolated from cystic fibrosis patients was investigated. Results showed that chitosan solution at 0.01, 0.05 and 0.10 mg/mL markedly inhibited the growth of B. cenocepacia Y10 although the antibacterial activity decreased with the increase of chitosan concentration. However, the antibacterial activity of chitosan solution against B. cenocepacia Y20 increased with the increase of chitosan concentration up to 0.05 mg/mL. In addition, the antibacterial activity of chitosan solution against B. cenocepacia strains was decreased by NaCl, CaCl2 and MgCl2. However, both ZnCl2 and FeCl3 significantly enhanced the antibacterial activity of chitosan solution regardless of the tested bacterial strains. Overall, the results indicated that chitosan-Zn or chitosan-Fe complex may be a promising candidate for novel antimicrobial agents in pharmaceutical industry.